Femtosecond response time measurements of a Cs2Te photocathode; Applied Physics Letters; Vol. 110, iss. 3 - Aryshev A. S. Aleksandr Sergeevich; Shevelev M. V. Mihail Viktorovich; Honda Y.; Terunuma Nobihiro; Urakawa Junji (2017, 2017)
Title screen